2021
DOI: 10.3390/insects12020163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Post-Emergence Weed Control in Honeybee Colonies Located in Different Agricultural Surroundings

Abstract: The honeybee Apis mellifera is exposed to agricultural intensification, which leads to an improved reliance upon pesticide use and the reduction of floral diversity. In the present study, we assess the changes in the colony activity and the expression profile of genes involved in xenobiotic detoxification in larvae and adult honeybees from three apiaries located in agricultural environments that differ in their proportion of the crop/wild flora. We evaluated these variables before and after the administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
2
0
1
Order By: Relevance
“…However, even when larvae are asymptomatic, differences in gene expression are still observed (Vázquez Latorre-Estivalis et al 2020a, 2020b. Follow-up experiments in agricultural settings showed that honey bee larvae are more vulnerable than adult workers to glyphosate (Macri et al 2021). The data summarized demonstrate that glyphosate exposure poses a significant threat to honey bees and their pollination services.…”
Section: Walter Farina: Glyphosate Exposure In Honey Bee Colonies: Ef...mentioning
confidence: 92%
“…However, even when larvae are asymptomatic, differences in gene expression are still observed (Vázquez Latorre-Estivalis et al 2020a, 2020b. Follow-up experiments in agricultural settings showed that honey bee larvae are more vulnerable than adult workers to glyphosate (Macri et al 2021). The data summarized demonstrate that glyphosate exposure poses a significant threat to honey bees and their pollination services.…”
Section: Walter Farina: Glyphosate Exposure In Honey Bee Colonies: Ef...mentioning
confidence: 92%
“…resistance to glyphosate at the oil palm plantation (Pasaribu et al 2017). Herbicide application has also affected non-target species such as earthworms (Kalkhoran et al 2022), snails (Fadhlaoui and Lavoie 2021), and the colonies' nutritional dan health status of honey bees (Macri et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Aplikasi herbisida dapat menekan pengaruh negatif gulma pada tanaman kentang (Barbaś et al 2020;Jabran et al 2023;Kalkhoran et al 2021). Akan tetapi penggunaan herbisida terus menerus dan dalam jangka waktu yang panjang dapat menyebabkan timbulnya resistensi gulma terhadap herbisida (Kurniadie et al 2021;Piasecki et al 2020;Rahmadi, 2021;Vulchi et al 2022), gangguan kesehatan lingkungan (He et al 2019;Hong et al 2022;Kwonpongsagoon et al 2021), bahkan dapat membahayakan organisme non target seperti koloni lebah (Macri et al 2021) dan organisme laut (Matozzo et al 2020;Sylwestrzak et al, 2021).…”
unclassified